Patterns of Adverse Childhood Experiences, Social Problem-Solving, and Mental Health Among Latina Immigrants - Alvarez, Carmen (Journal of interpersonal violence, 2022)
Researchers have established the long-term negative impact of adverse childhood experiences (ACEs) on mental health. Evidence also shows that different types of ACEs often co-occur and that ACEs profiles have differential impact on mental health. However, this prior research has often omitted first-generation Latino immigrants?a growing segment of the population, with potentially higher risk for ACEs, decreased access to mental health services, and increased risk for remaining in poor mental health. In this study, we conducted a cluster analysis using a sample of 336 Latina immigrant to examine: (1) patterns of ACEs, and (2) the mediating role of social problem-solving in the association between ACEs and mental health (depression, anxiety, and post-traumatic stress disorder symptoms [PTSD]) and life satisfaction. We identified 5 clusters: (a) Global ACEs (n = 52, 15.5%), (b) Community Violence and Physical Abuse (n = 80, 23.8%), (c) Physical and Emotional Abuse (n = 72, 21.4%), (d) Household Dysfunction with Physical and Emotional Abuse (n = 56, 16.7%), and (e) Low ACEs (n = 76, 22.6%). The clusters differed by social problem-solving, chronic life burden, mental health, and life satisfaction. Compared to the Low Abuse cluster, the Community Violence and Physical Abuse, and Global ACEs clusters were significantly more likely to have higher depression, anxiety, and PTSD symptoms. Social problem-solving was independently associated with all mental health variables and life satisfaction, and mediated the association between ACEs and depression and anxiety for those in the Community Violence and Physical Abuse cluster. Our study sheds light on how ACEs are experienced by Latina immigrants. Social problem-solving also emerged as a significant determinant of mental health and life satisfaction, and may be a point of intervention for improving mental health in this population.